Recent advances on bioreceptors and metal nanomaterials-based electrochemical impedance spectroscopy biosensors - Chen, Zibo; Jin, Hui-Hui; Yang, Zhugen; He, Daping (Springer, 2023)
Metal-based nanomaterials have a wide range of applications in energy conversion, catalysis, bioimaging, and sensors. In our review, we mainly introduce metal nanomaterials-based electrochemical impedance spectroscopy (EIS) biosensors in medical healthcare, environmental monitoring, and food safety instructively, with collecting and analyzing the current achievement of predecessors. In general, metal nanomaterials-based EIS biosensors can be divided into four components, in which bioreceptors and metal nanomaterials transducers are vital for designs. Bioreceptors and metal nanomaterials determine the feasibility, specificity, sensitivity and simplicity of manufacturing and operations. With the demonstration and discussion of bioreceptors and metal nanomaterials of biosensors in different fields, our review aims to assist brief acknowledgement of current state-of-the-art achievement and provide our insights for the future development.
Keywords: Metal nanomaterials; Electrochemical impedance spectroscopy (EIS); Biosensors; Bioreceptors